HYGIENIC EVALUATION OF THE BACTERIAL CONTAMINATION OF A MULTIDISCIPLINARY HOSPITAL IN DONBASS IN MODERN CONDITIONS. PART I. COMPARISON OF THE PRE-WAR AND WAR PERIODS - Бондаревский-Колотий, Вячеслав Александрович; Ластков, Дмитрий Олегович; Сихарулидзе, Анна Григорьевна; Щербина, Юлия Владимировна (Medicine in Kuzbass, 2024)
A comparative hygienic assessment of bacterial contamination of air, washes, sterility of materials, skin of the operating field and surgeons’ hands in the units of a multidisciplinary hospital in the pre-war period and after the beginning of the local military conflict is given. The growth of bacterial contamination of the air environment, including the content of Staphylococcus aureus, swabbing and deterioration of the sterility index during the war period was found.